Communication Strategy in Improving Satisfaction E-Commerce Customers - Budi Alamsyah Siregar (Almana : Jurnal Manajemen dan Bisnis, 2021)
At this time, product marketing competition is experiencing dynamic changes and is getting higher. Therefore, companies are required to choose the right marketing strategy to support increased product sales. Business communication is one of the strategies that companies can apply. This is because business communication is an attempt to provide information to customers. Accuracy in implementing business communication will cause positive customer reactions to the products being sold. This study aims to determine how the implementation of business communication strategies by e-commerce companies in Indonesia creates customer satisfaction with the services. This study uses a qualitative and quantitative method approach—research data, using primary and secondary data. Primary data were obtained directly from research respondents through interviews and questionnaires. On the other hand, secondary data is obtained based on existing library sources. Data collection, obtained from 30 customers who use e-commerce purchases. Data analysis was performed using descriptive techniques and a simple linear regression test. The results showed that the involvement of managers and field staff in providing services to customers increased sales. This finding shows that the right business communication strategy has a positive impact on customer trust reactions, which in turn increases product sales.